Implementasi Toilet Training sebagai Praktik Pedagogis Penumbuhan Kemandirian Anak Usia 3–4 Tahun di Raudhatul Athfal: Studi Kasus Tunggal di PG-RA Alhidayah Logam Kota Bandung - Zahwa Nur’Izzati Shifa; Tepi Mulyaniapi; Wulan Tini (Journal of Islamic Early Childhood Education (JOIECE): PIAUD-Ku, 2026)
Toilet training is the earliest institutionalized site at which young children negotiate autonomy, yet international literature treats it predominantly as a clinical problem of continence acquisition and rarely as an educational practice embedded in an early childhood curriculum. Research examining toilet training as a pedagogical and character-forming process within faith-based early childhood settings remains scarce, particularly through in-depth single-case designs. This study describes and interprets the implementation of toilet training for one child aged 3–4 years at PG-RA Alhidayah Logam, Bandung, and its relation to emerging indicators of autonomy. A qualitative single-case design was employed. The subject was a boy aged three years and eight months; the mother and the classroom teacher served as supporting informants. Data were gathered through participant observation, semi-structured interviews, and documentation over eight weeks, and analyzed using the interactive model of Miles, Huberman, and Saldaña. Trustworthiness was established through source and technique triangulation, member checking, and an audit trail. Three findings emerged. Obstacles clustered around the child’s physical and psychological readiness and inconsistent parental follow-through. Observable behaviors included bodily signaling, verbal request, self-dressing, and the habituation of supplication. Implementation proceeded through preparation and introduction, scheduled toileting, and hygiene instruction, a sequence that hybridizes child-oriented readiness rhetoric with structured-behavioral scheduling. The account repositions toilet training from a behavioral intervention to a curricular practice in which autonomy and religiously framed hygiene are cultivated together, while its single-case scope precludes any claim of general effectiveness